The The Influence of Sharia Commercial Bank Financing on Profitability - Indrayanti, Shania Pasha; Mranani, Muji; Dewi, Veni Soraya (Universitas Muhammadiyah Yogyakarta, 2023)
Introduction - The theme of this research is the effect of financing on the profitability of Islamic Commercial Banks. Profitability is the company's ability to generate profits with all the capital owned by the company. Companies or banks that have a high rate of return on investment use relatively small debt because the high rate of return allows the company to finance most of its internal funding.Objective – This research was conducted with the aim of analyzing the effect of mudharabah, musyarakah, murabahah, istishna'dan ijarah financing on profitability in Islamic commercial banks registered with OJK for the 2017-2021 period Methodology - This research uses quantitative research. The data used is secondary data obtained from the annual financial reports of Islamic commercial banks registered with the Financial Services Authority (OJK) for the 2017-2021 period. The number of samples used was 28 samples obtained using purposive sampling method. The analysis technique used is multiple linear regression with the help of the SPSS 25 program. Findings - The research results obtained show that the financing variables mudharabah, murabaha and ijarah have no effect on profitability, while musyarakah and istishna' variables have a negative effect on profitability. Implications - The results of this study are expected to improve banking performance from financial and non-financial aspects.